AN ANALYSIS OF IMPLEMENTATION NURSERY COMPETENCE STANDARD IN THE SERVE UNIT OF ACHMAD MOCHTAR HOSPITAL BUKITTINGGI 2018 - Rahmat Syukri (HUMAN CARE JOURNAL, 2019)
Competence is the foundation for most professional practice frameworks, even though concepts are difficult to be understood. Competency models vary and are internal, individual and approach attributes about what is known and what can be done by individuals, to social approaches to external activities that focus on activities or functions that need to be carried out competently.               The purpose of the research is to find out the analysis, describe and interpret the nurse's competence with the implementation of the nurse's authority in the implementation of nursing actions in Achmad Mochtar government Hospital Bukittinggi of service unit in 2018. This type of research is qualitative by approaching with a phenomenological study. The sampling technique uses purposive sampling with 11 participants. Interview conducted once time. Data analysis on the phenomenological approach according to Creswell (2013) uses a systematic coding process.               The research results found that participants have already a certificate of nursing competence obtained through competency exams, training and workshops. The competency certificates such as BTCLS and STR. The average participant does not have a competency certificate outside nursing               Based on the results of the research, it can be concluded that nursing services provided by nurses have been professionally provided to patients who need nursing care. This is evidenced by the implementation of nursing care that is in accordance with the process of nursing care. This research is expected to be a consideration for the hospital so that the operational standard procedure for delegation of doctors' authority to the nurses of Achmad Mochtar Government Hospital Bukittinggi needs to be more detailed and firm and the implementation of the doctor's authority to nurses in writing form.   Keywords: serve units, nurses, competency standards